Dzīvnieku tiesību aizsardzības krimināltiesiskie aspekti - Pupelis, Guntars (Latvijas Universitāte, 2010)
Bakalaura darba mērķis ir izvērtēt dzīvnieku tiesību aizsardzības problēmas un pētīt attiecīgo tiesu praksi. Darba uzdevums ir apzināt šīs grupas nodarījumu tiesisko reglamentāciju normatīvajos aktos un iepazīties ar tiesu praksi, norādot uz judikatūru. Bakalaura darbs sastāv no trīs nodaļām un to apakšnodaļām, ievada, kopsavilkuma, izmantotās literatūras un tiesību avotu saraksta, kā arī anotācijas angļu valodā un pielikuma. Pirmajā nodaļā tiek analizēts dzīvnieku tiesību aizsardzības jēdziens un tā izpratne Latvijā. Kā arī tiek pētīta Krimināllikuma 230. panta vēsturiskā attīstība mūsu valstī. Otrajā nodaļā autors analizē Krimināllikuma 230. pantā paredzētā noziedzīgā nodarījuma – cietsirdīgas izturēšanās pret dzīvnieku - sastāvu – objektu un objektīvo pusi, subjektu un subjektīvo pusi. Trešā nodaļa ir veltīta ārvalstu krimināllikumu izpētei un to normu analīzei, kas attiecas uz dzīvnieku tiesībām. Apkašnodaļās autors pēta arī labturības noteikumu attīstību Latvijā, kā arī likuma grozījumus par labu rituālaijai kaušanai. Izpētes un analīzes laikā ir izdarīti secinājumi par Krimināllikuma 230. panta piemērošanu tiesu praksē, kā arī par ārvalstu pieredzi dzīvnieku tiesību aizsardzības jomā. Ir izdarīti vairāki priekšlikumi, lai uzlabotu likuma normas un veicinātu sabiedrības izpratni par dzīvnieku tiesībām.

Bachelors work is about legal situation in the field of animal rights ir Latvia and criminal aspects of it. Author has studied many national court decidions and laws, through out the period from 1998-2010. In this period of time Latvian Criminal law has developed as it is today, that is why author has focused on development in animal rights in the Criminal Law. Also, athor has studied many Criminal laws of other countries, trying to find the best solutions for Latvian Criminal Law, to make the animal rights more serious and develop them in to a new level. In the first chapter author seeks to find how does animal protection concept, role and regulation in Latvia work, why there are so many acts of violence against animals and why the court system is so reckless in these cases. Author also studies the only article in Latvian Criminal law, which provides penalty against violation of animal rights. The study is based on historical development and trends of Latvian Criminal law, beginning with Penal code of year 1903, until today’s version of it. The second chapter is based on the objective and subjective set of features in Latvian Criminal law article 230. Also in this chapter author is trying to give solutions, how to improve the article 230. in terms of animal rights improvement. In the third chapter author is trying to compare Criminal laws and Penal codes of many European countries and the United States of America, with the Criminal law of Latvian Republic. Also author studies the welfare rules in Latvia and other countries, drawing a big attention to the newest changes in these rules. The fourth chapter of bachelors work is more of an essay type article about the legal status of animals. Finally the author gives his best insights about this work in for of thesis and proposals. Lastly the author shows the references used in the making of this bachelors work.
Criminal aspects of protection of animal rights
Keywords: Juridiskā zinātne